1,1′-[(1,3-Dihydroxypropane-2,2-diyl)dimethylene]dipyridinium bis(hexafluorophosphate) - Ai-lin Yuan (Acta Crystallographica Section E, 2011)
The title compound, C15H20N2O22+·2PF6−, was prepared by anion exchange of two bromide ions in the ionic liquid 2,2′-bis-(pyridinium-1-ylmethyl)-propane-1,3-diol dibromide with potassium hexafluorophosphate. The two pyridine rings are planar (r.m.s. deviations = 0.008 and 0.00440 Å) and make a dihedral angle of 44.0 (2)°. Intermolecular O—H...F and C—H...F interactions occur. The four F atoms in each anion were refined as disordered over two sets of sites with an occupancy ration of 0.700 (19):0.300 (19).